PELATIHAN KEWIRAUSAHAAN DAN PENYUSUNAN BUSINESS PLAN UNTUK MENINGKATKAN MINAT BERWIRAUSAHA SISWA MADRASAH FAR’USSA’ADAH ARABIYAH TANJUNG JABUNG BARAT - Zuhratul Aulia; Nisya Puspita Safitri; Sugiharto; Khairunnisa (Berajah Journal, 2025)
Entrepreneurship development has become an important agenda in Indonesia to increase the number of entrepreneurs and strengthen the national economy. One strategic effort is introducing entrepreneurial education at the school level to cultivate entrepreneurial mindset and skills among students. This community service activity aimed to provide entrepreneurship training and business plan preparation for students of Madrasah Far’ussa’adah Arabiyah in Tanjung Jabung Barat. The activity involved approximately 50 third-grade students and was conducted over two days using lecture, tutorial, discussion, and mentoring methods. The program consisted of entrepreneurship education, business idea development, and practical training in preparing business plans. The results showed that the training improved students’ understanding of entrepreneurship concepts and the importance of business planning before starting a business. Students were able to formulate simple business plans including business profiles, market analysis, operational planning, and marketing strategies. However, the financial planning aspect still required further guidance. Overall, this program successfully enhanced students’ entrepreneurial awareness and motivation. Future programs are recommended to include advanced training in financial analysis and business incubation to support sustainable student entrepreneurship development.